MIMESIS E RITUAL: BASES DO AGIR SOCIAL, FUNÇÕES E FENÔMENOS SOCIAIS E CULTURAIS NA EDUCAÇÃO (Revista Contexto & Educação, 2021)
This paper aims to analyse mimetic foundations of social acting and appropriation of world through ritual, ritual functions in education and to discuss on social and cultural phenomena in education.  Which are mimetic foundations of social acting and appropriation of world through ritual? Which are ritual functions in education? How does relation of mimetic process to ritual as phenomena of social and cultural mimesis establish? The theoretical framework on mimesis and ritual is based on anthropological and German educational anthropology approaches. The method to analyse is hemrneutic content analysis, i.e., to analyse/meditate on choosen textual material and to perform an analysis of general sense of texts.  The results point out that mimetic foundations of social acting lead to, through ritual, appropriation of world and establishment of individual. The ritual functions involve: a)social relations, social reality,  power relations and context; b) performance and bodily practices; c) time and space, repetition and sequentiality; d) alterity, synchronicity, diachrony and social and cultural changes.